PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Ibnu Waliq; Ravindra Safitra Hidayat; Feby Lukito Wibowo (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to determine the influence of product quality, price perception, and promotion on purchasing decisions at Baihaqi Clothing Muslim Tanah Abang, Central Jakarta. This type of research is quantitative. The population in this study is unknown. The sample used was 100 respondents, with the sampling method using a non-probability sampling technique with the accidental sampling method. The data collection technique is through a questionnaire with a Likert scale which has been processed using SPSS Version 23 software. The data analysis used is validity and reliability testing, classical assumption testing, hypothesis testing and multiple linear regression. The results of this research show that the variables product quality, price perception and promotion, each have a significant influence on purchasing decisions.